2009
DOI: 10.1007/s00417-009-1128-0
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical and immunohistochemical profile of human and rat ocular medial rectus muscles

Abstract: Purpose To compare the organization of human and rat ocular medial recti muscles (MR). Methods The cryosections of human and rat MR were processed for myofibrillar ATPase (mATPase), succinate dehydrogenase and glycerol-3-phosphate dehydrogenase. To reveal myosin heavy chain (MyHC) isoforms, specific monoclonal antibodies against MyHC-1/β-slow, α-cardiac (-α), -2a, -2x, -2b, -extraocular (eom), -embryonic (-emb) and -neonatal (-neo) were applied. The MyHC gene expression was studied by in situ hybridization in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 43 publications
(61 reference statements)
3
13
0
1
Order By: Relevance
“…Nevertheless, in this study we have confirmed that the range of MyHC gene expression is wider in the laryngeal muscles compared to the limb muscles and is similar to that found in the extraocular muscles [Wieczorek et al, 1985;Kjellgren et al, 2003;Stirn Kranjc et al, 2009].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Nevertheless, in this study we have confirmed that the range of MyHC gene expression is wider in the laryngeal muscles compared to the limb muscles and is similar to that found in the extraocular muscles [Wieczorek et al, 1985;Kjellgren et al, 2003;Stirn Kranjc et al, 2009].…”
Section: Discussionsupporting
confidence: 74%
“…However, contrary to these studies, we recently demonstrated the expression of both, i.e. MyHC-2b transcripts and MyHC-2b isoform, in extraocular muscles by in situ hybridization and immunohistochemistry, respectively Stirn Kranjc et al, 2009].…”
Section: Abbreviations Used In This Papermentioning
confidence: 80%
“…To determine expression of unconventional MHC we reacted tissue with Ab 4A6 (Developmental Studies Hybridoma Bank, Iowa, DSHB), which in rabbits and likely baboons and humans is specific for MHCeom (Kjellgren et al, 2003; Lucas & Hoh, 1997; Sokoloff, Daugherty, & Li, 2010), Ab MYH6 (Sigma-Aldrich), which in humans is reported to be specific for MHCac (Stirn Kranjc, Smerdu & Erzen, 2009) and Ab S46 (DSHB), which reacts with putative MHCst in adult human muscle spindles and human extraocular muscles but does not cross-react with MHCac or MHCI in adult catarrhine primate muscle (Sokoloff, Yang, Li, & Burkholder, 2007b). …”
Section: Methodsmentioning
confidence: 99%
“…Here we tested the putative anti-MHCac Ab MYH6 (Stirn Kranjc et al, 2009) by IHC. Ab MYH6 at dilution of 1:5 and 1:25 weakly-to-strongly labeled control MS (for presence of MHCac in MS see Liu et al, 2003) in GG and weakly to moderately labeled extrafusal fibers positive for Ab A4.84 (Figures 2D, 2E).…”
Section: Methodsmentioning
confidence: 99%
“…The very fast MHC IIb isoform has been detected in cheetah, pig and llama skeletal muscle, with its expression in other larger animals (bovine, human and horse) absent and restricted to specialized muscles (e.g. eye muscles) (Quiroz-Rothe and Rivero, 2001;Lefaucheur et al, 2002;Toniolo et al, 2005;Stirn Kranjc et al, 2009;Hyatt et al, 2010).…”
Section: Introductionmentioning
confidence: 99%